Study of association between the serum lipid profile and age-related macular degeneration in a tertiary care centre of Central UP - Husain, Ahmad; Singh, Brijesh; Ranjan, Ravi; Jawad, Kalbe; Sami, Ifsa; Verma, Vivek Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Age-related macular degeneration (ARMD) is the major challenge in the new millennium in the developing countries as the size of elderly population continues to rise due to betterment of medical facilities and increased life expectancy. Lipids are implicated in the pathogenesis of ARMD. The relationship between systemic lipids and ARMD has not been well characterized, especially in rural population. The objective was to investigate the relationship between serum lipids and ARMD in older adults. Methods: In this case-control study, 300 adults, aged ≥50 years, 150 each among cases and controls were included in the study. Mean lipids values between cases and controls were compared. Results: Mean age of cases was 62.45±8.472 years and mean age of controls was 61.89±8.51 years. Among 150 cases, 124 (82.66%) cases were of dry ARMD while 26 (17.33%) cases were Wet ARMD. Author found that 38 cases among total cases (25.33%) and 15 individuals (10%) among controls had altered lipid profile. All mean lipid values were higher among cases compare to controls (p>0.05), while the mean of VLDL, TG and TG/HDL were significantly raised showing positive association (p<0.05). Conclusions: Present study showed that high levels of serum lipid values especially VLDL, TG and TG/HDL positive association with an increased risk for development of ARMD, implying that strategies reducing serum lipid levels may be useful to prevent the development of the disease.